Techno-Economic Investigation of a Thermal Cure Center Excess Heat Recovery System for Producing Hot Water for a Hotel in Antsirabe Madagascar - Rakotondramiarana, Hery Tiana; Radanielina, Mamy Harimisa; Ramananjatovo, Andriamaholisoa Yvan (Journal of Technology Innovations in Renewable Energy, 2015)
Energy saving is a significant feature to take in account in the choice of renewable energy technologies to use. This paper techno-economically investigates an excess heat recovery system that is proposed to be installed in a thermal cure center geothermal source for producing domestic hot water to be conveyed through piping to a nearby three star hotel located in Antsirabe Madagascar. For that purpose, the hotel hot water needs were determined by using an available online free code, called Solo, and the effectiveness-NTU method was used to size the plate heat exchanger to be used to recover the geothermal heat. The proposed hybrid geothermal solution performance was compared with that of hybrid solar energy water-heaters in terms of electricity consumption related to water temperature adjustment. It follows from comparison results that the proposed hybrid geothermal solution is more profitable and allows about 73.2 (%) of electric energy saving while it is 54.9 (%) for hybrid solar option. Besides, economic evaluation confirmed that the geothermal installation allows a shorter return on investment more favorably.